Local Wisdom for Global Leadership - Djovana, Amalya El Fatihah; Nikmah, Lailatul (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2025)
The current inquiry addresses the 21st-century global leadership crisis triggered by the dominance of rationality devoid of spirituality. In response, this work explores the pesantren (Islamic boarding school) as a vital source of local wisdom capable of producing leaders characterized by moral integrity and inner consciousness. This article aims to investigate the internalization of four foundational pillars—intention (niat), conviction (yakin), gratitude (syukur), and sincerity (ikhlas)—within the Management, Training, and Leadership (MTL) programs for students (santri). Utilizing a qualitative phenomenological approach, the investigation gathered data through participant observation and in-depth interviews with both students and mentors. The findings demonstrate that the application of these four pillars fosters self-awareness, integrity, empathy, and social commitment aligned with global leadership standards. The present analysis concludes that this internalization process is not merely character building but a spiritual journey that guides students to manifest love and harmony in leadership actions. Ultimately, the study positions pesantren-based local wisdom as a strategic bridge toward a more civilized, compassionate, and spiritually-grounded global leadership order